Understanding female athlete disordered eating and recovery through narrative turning points in autobiographies. (January 2019) - McGannon, Kerry R.; McMahon, Jenny
Abstract: Purpose: To use narrative inquiry to study disordered eating meanings and experiences of elite female athletes struggle and recovery as socially constructed within stories. Published autobiographies of two high profile elite athletes were explored as socio-cultural sites of analysis to expand understanding of disordered eating struggle and recovery over time. Design: A thematic narrative analysis grounded in social constructionist narrative inquiry was used to identify broad cultural narratives and turning points (i.e., psycho-social life events linked to struggle/insight) within the narratives, in two elite female swimmers' autobiographies. Findings: Two cultural narratives were identified: performance narrative and struggle and personal growth narrative . These narratives framed key turning points within the stories -- body and relationship turning points (linked to struggle) and emotional and body acceptance turning points (linked to recovery). Conclusions: These findings build upon previous narrative and autobiographical research in sport psychology which shows the value in studying elite athletes' stories as theoretical, methodological and pedagogical resources to learn more about athlete health. The present study expanded understanding of gendered disordered eating meanings of struggle and recovery within elite swimming culture as nuanced personal and cultural processes across two athletes' careers. Such work further opens up ways to use autobiographies as pedagogical resources to harness relational narratives to facilitate female athlete's recovery. Highlights: Understandings of disordered eating struggle and recovery for elite female athletes are extended. Disordered eating meanings were constructed in performance and personal growth narratives. Body related and relationship narrative turning points add to struggle and constrain recovery. Emotional and body acceptance turning points open up recovery as a fluid process.